2003
DOI: 10.1590/s0303-76572003000100007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da exposição ocupacional ao chumbo em uma metalúrgica um estudo transversal

Abstract: OBJETIVO: Avaliar o nível de exposição ocupacional em uma metalúrgica de chumbo, através da determinação dos indicadores biológicos de exposição e efeito, com o objetivo de estabelecer um mapeamento das áreas de risco dentro da planta industrial. METODOLOGIA: Estudo transversal incluindo 195 trabalhadores de uma metalúrgica primária de chumbo, localizada no Estado da Bahia-Brasil, e um grupo de referência de 65 indivíduos. Nos grupos de expostos e controle foram realizadas as dosagens dos indicadores biológico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The nonlinear positive correlation observed here has also being demonstrated elsewhere. For example, Menezes‐Filho et al, (2003) evaluated workers in a primary smelting company in Santo Amaro, Bahia, Brazil, and similar behavior was observed. As in our study, an inflection point of ZnPP was observed with PbB levels between 20 and 30 μg/dl.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The nonlinear positive correlation observed here has also being demonstrated elsewhere. For example, Menezes‐Filho et al, (2003) evaluated workers in a primary smelting company in Santo Amaro, Bahia, Brazil, and similar behavior was observed. As in our study, an inflection point of ZnPP was observed with PbB levels between 20 and 30 μg/dl.…”
Section: Discussionmentioning
confidence: 73%
“…It has been shown to habe a significant positive correlation between ZnPP and blood PbB levels above 20–30 μg/dl (Martin et al, 2004). Menezes‐Filho, Carvalho, and Spínola (2003) carried out a study with primary smelter workers in Brazil and observed significant nonlinear positive correlation between PbB and ZnPP levels.…”
Section: Introductionmentioning
confidence: 99%